An Analysis to the Link between Foreign Trade and Sectorial Economic Growth in Iraq - ABDULSAHIB, Ahmed Saddam (Theoretical and Practical Research in Economic Fields, 2024)
This research aims to analyse the link between oil export, commodity imports and other major sectors such as agricultural, manufacturing and service sectors over the period spanning from 2004 to 2020. So, it aims to extrapolating and analyse the role of Iraqi economic policy toward the diversification. Therefore, it tries to assess the governmental economic performance in utilizing oil revenues for reinforcement the manufacturing and agriculture sectors. For this purpose, the Granger causal relationship is used to find out the magnitude of the variables examined. The expected results will depict an assessment of the public economic policy. Thus, this paper tries to extrapolate to what extent the oil revenues can be circulated to activate the local economic sectors and enhance level of economic diversification in Iraq as an announced policy during the period studied.